Randomized phase III study of temozolomide versus dacarbazine in the treatment of patients with advanced metastatic malignant melanoma - Middleton, Mark R.; Schadendorf, Dirk (Journal of clinical oncology, 2016)
Purpose: To compare, in 305 patients with advanced metastatic melanoma, temozolomide and dacarbazine (DTIC) in terms of overall survival, progression-free survival (PFS), objective response, and safety, and to assess health-related quality of life (QOL) and pharmacokinetics of both drugs and their metabolite, 5-(3-methyltriazen-1-yl)imidazole-4-carboximide (MTIC). Patients and methods: Patients were randomized to receive either oral temozolomide at a starting dosage of 200 mg/m2/d for 5 days every 28 days or intravenous (IV) DTIC at a starting dosage of 250 mg/m2/d for 5 days every 21 days. Results: In the intent-to-treat population, median survival time was 7.7 months for patients treated with temozolomide and 6.4 months for those treated with DTIC (hazards ratio, 1.18; 95% confidence interval [CI], 0.92 to 1.52). Median PFS time was significantly longer in the temozolomide-treated group (1.9 months) than in the DTIC-treated group (1.5 months) (P = .012; hazards ratio, 1.37; 95% CI, 1.07 to 1.75). No major difference in drug safety was observed. Temozolomide was well tolerated and produced a noncumulative, transient myelosuppression late in the 28-day cycle. The most common nonhematologic toxicities were mild to moderate nausea and vomiting, which were easily managed. Temozolomide therapy improved health-related QOL; more patients showed improvement or maintenance of physical functioning at week 12. Systemic exposure (area under the curve) to the parent drug and the active metabolite, MTIC, was higher after treatment with oral temozolomide than after IV administration of DTIC. Conclusion: Temozolomide demonstrates efficacy equal to that of DTIC and is an oral alternative for patients with advanced metastatic melanoma.